Analisis Perusahaan Jasa Konstruksi Terafiliasi dalam UU Jasa Konstruksi dan UU Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Febrianto, Ika; Suparji, Suparji; Hidayat, Yusuf (Jurnal Bedah Hukum, 2023)
The economy of a country is closely related to economic transactions carried out by actors, namely producers, sellers and buyers. Such conditions increase the value of efficiency and reduce government costs due to community participation. This is in accordance with the objectives of Law number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and Law number 2 of 2017 concerning Construction Services. Therefore, it is necessary to examine the compatibility between Article 44 of the Construction Services Law and Article 22 of the Antimonopoly and Unfair Business Competition Law and the position of affiliated construction companies in tenders for government procurement of goods and services using the rule of reason and per se illegal approach. The research method in this journal is normative juridical, library research and comparative study. So it can be concluded that article 44 of the Construction Services Law prohibits affiliation between service users and service providers (collutive vertical) with an illegal per se approach while article 22 of the Antimonopoly and Unfair Business Competition Law prohibits affiliation with a rule of reason approach. The method of inviting or directly appointing a service provider can create an affiliation relationship between the user and the service provider which can be interpreted as a form of nepotism. All parties involved in the process of procuring goods and/or services by the government must follow the principles of fair business competition.